Pre-Clinical Cell-Based Therapy for Limbal Stem Cell Deficiency - Sehic, Amer (J Funct Biomater, 2015)
The cornea is essential for normal vision by maintaining transparency for light transmission. Limbal stem cells, which reside in the corneal periphery, contribute to the homeostasis of the corneal epithelium. Any damage or disease affecting the function of these cells may result in limbal stem cell deficiency (LSCD). The condition may result in both severe pain and blindness. Transplantation of ex vivo cultured cells onto the cornea is most often an effective therapeutic strategy for LSCD. The use of ex vivo cultured limbal epithelial cells (LEC), oral mucosal epithelial cells, and conjunctival epithelial cells to treat LSCD has been explored in humans. The present review focuses on the current state of knowledge of the many other cell-based therapies of LSCD that have so far exclusively been explored in animal models as there is currently no consensus on the best cell type for treating LSCD. Major findings of all these studies with special emphasis on substrates for culture and transplantation are systematically presented and discussed. Among the many potential cell types that still have not been used clinically, we conclude that two easily accessible autologous sources, epidermal stem cells and hair follicle-derived stem cells, are particularly strong candidates for future clinical trials.